(untitled) (World Bulletin of Management and Law, 2024)
This article describes the documents adopted on the provision and protection of the rights of persons with disabilities and their importance in ensuring the rights of persons with disabilities, as well as the process of codification of legal sources. At the same time, the principles of protecting the rights of persons with disabilities in our national legislation and the Constitution of the Republic of Uzbekistan are provided